The Effect of Accountability, Responsibility, Independence, and Fairness on the Performance of Klungkung LPDs - Putu Kepramareni; Sagung Oka Pradnyawati (Asia Pacific Journal of Management and Education (APJME), 2021)
The progress of a country can be seen from its economic growth level. One of the financial institutions that helps the economic sector at the traditional village level in Bali Province is the Village Credit Institution (LPD). LPD performance describes its goal achievement. This research aims to determine the LPD performance of Klungkung with several variables such as accountability, responsibility, independence, and fairness tested using multiple linear regression analysis. The findings show that accountability does not affect LPD performance while responsibility, independence, and fairness positively affect LPD performance.